2022
DOI: 10.1007/s40120-022-00360-w
|View full text |Cite
|
Sign up to set email alerts
|

The Cure SMA Clinical Trial Experience Survey: A Study of Trial Participant Perspectives on Clinical Trial Management and Patient-Centric Management Practices

Abstract: Introduction Understanding clinical trial experiences can illuminate opportunities to optimize trial design and management, with potential benefits for recruitment and retention. This study sought to better understand clinical trial participant experiences and attitudes within spinal muscular atrophy (SMA), and how the evolving treatment landscape and participant characteristics may predict attitudes. Methods A survey was developed following a review of published litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Verhaart et al (2019) found that communication of results was considered important, but only received by 26% of participants [45]. The desire for better access to information is not unique to FSHD, and was noted in a recent study regarding patient preferences in spinal muscular atrophy [46]. Whilst educational sources are available, patients are not sufficiently informed of where to access this.…”
Section: Discussionmentioning
confidence: 99%
“…Verhaart et al (2019) found that communication of results was considered important, but only received by 26% of participants [45]. The desire for better access to information is not unique to FSHD, and was noted in a recent study regarding patient preferences in spinal muscular atrophy [46]. Whilst educational sources are available, patients are not sufficiently informed of where to access this.…”
Section: Discussionmentioning
confidence: 99%